The influence of individual differences in the processing of words expressing discrete emotions: data from a large-scale study - Juan Haro; José Antonio Hinojosa; Pilar Ferré (Scientific Reports)
Abstract In this study, we addressed the influence of individual differences in personality traits measured trough a Big Five personality test, and sociodemographic variables such as age or gender, in the processing of words conveying discrete emotions. To this aim, we relied on data from a large-scale lexical decision task in Spanish. The analyses with linear mixed models revealed several interactions between emotional content and both personality traits and sociodemographic factors during word recognition. In this sense, there was a facilitation for fear-related words, mainly in male participants. Also, disgust interacted with agreeableness and conscientiousness, showing an inhibition for disgust-related words in participants scoring low in agreeableness or high in conscientiousness. Sadness-related words were processed more slowly in men, while this effect was absent in women. Finally, happiness-related words showed an interaction with openness to experience, age and gender. We discuss the complex interplay between the emotional connotation of words and individual differences. All in all, our findings emphasise the need to take individual characteristics into account when examining emotional word processing.